Optimization of REMS Program Compliance in a Large Academic Health System - Audrey B Kostrzewa (University of Minnesota Libraries Publishing, 2021)
Ensuring compliance with all applicable Risk Evaluation and Mitigation Strategies (REMS) programs within a health system is challenging. These FDA-mandated programs are numerous, unique, and ever-changing. Actions require several stakeholders and moving parts. In addition, the effectiveness and impact of these programs has been challenged and is not always clear, which hampers buy-in and therefore compliance. F&MCW is a health network in southeastern Wisconsin that includes five hospitals and almost 40 clinics. Since 2014, several system-wide approaches to medication use, including formulary alignment and REMS program optimization, have taken place with an over-arching goal of providing efficient, safe, and consistent care for the patients and populations served. This manuscript describes the steps that took place over the past six years or so related to REMS program optimization. It also offers practical tips for other health systems based on lessons learned through this one institution's experiences.